2007
DOI: 10.1373/clinchem.2006.073668
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between C-Reactive Protein and Atherosclerotic Risk Factors and Oxidative Stress Markers Among Young Persons 10–18 Years Old

Abstract: Background: This study was undertaken to determine the association of serum C-reactive protein (CRP) with generalized and abdominal obesity, body fat composition, the metabolic syndrome, and oxidative stress markers among young people. Methods:We conducted a population-based study of 512 young people, aged 10 -18 years. We obtained anthropometric and blood pressure measurements. Fasting blood sugar, total cholesterol (TC), HDL-cholesterol, triglycerides, CRP, malondialdehyde (MDA), and conjugated diene (CDE) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
6
41
1
Order By: Relevance
“…Roh et al (33) evaluated obese adolescents and observed inflammatory characteristics similar to those of obese adults. In addition, Kelishadi et al (34) observed that CRP in adolescents increased with abdominal obesity, and this elevation was associated with high levels of oxidative biomarkers (malondialdehyde and conjugated dienes). Our results demonstrated that CRP increased as a function of BMI, WC, and AC, which have been used to evaluate adiposity.…”
Section: Ratiomentioning
confidence: 99%
“…Roh et al (33) evaluated obese adolescents and observed inflammatory characteristics similar to those of obese adults. In addition, Kelishadi et al (34) observed that CRP in adolescents increased with abdominal obesity, and this elevation was associated with high levels of oxidative biomarkers (malondialdehyde and conjugated dienes). Our results demonstrated that CRP increased as a function of BMI, WC, and AC, which have been used to evaluate adiposity.…”
Section: Ratiomentioning
confidence: 99%
“…We have previously documented an increase in serum Creactive protein (CRP) 5 and oxidative stress markers in children with abdominal obesity, suggesting that ox-idative stress and CRP may be associated with the early inflammatory processes of atherosclerosis (7,9 ).…”
mentioning
confidence: 99%
“…In a population-based study, Kelishadi et al reported a significant correlation between CRP and oxidative stress markers (MDA and conjugated diene) in 512 children and adolescents aged 10-18 years with abdominal obesity. 7 Another study by Oliver et al demonstrated simultaneous elevations in inflammatory and oxidative status in overweight and obese peripubertal children, when compared to healthy controls matched for age, gender, and fitness level. Obese children displayed significantly increased inflammatory cytokine (interleukin-6/IL-6) and systemic levels of lipid peroxidation (F2-isoprostanes).…”
Section: Discussionmentioning
confidence: 97%
“…6 A previous study documented that obese children with upper quartiles of C-reactive protein (CRP) and oxidative stress markers were more likely to have metabolic syndrome and abnormal lipid profiles, suggesting that inflammation and oxidative stress are interrelated, and might be associated with harmful health effects. 7 To the best of our knowledge, no previous study has evaluated the levels of inflammatory and oxidative stress markers among overweight, obese, and severely obese prepubescent children. Therefore, the aim of this study was to compare high-sensitivity C-reactive protein (hsCRP) and malondialdehyde (MDA) levels by the severity of obesity in prepubertal children aged 6 to 10 years.…”
mentioning
confidence: 99%